Descoberta de preços e especulação no mercado de milho brasileiro - Raniro, Luisa Rasera (Universidade Federal de São Carlos, 2018)
University of São Carlos, Sorocaba, 2018. Since the 2000s, several changes occurred in the Brazilian and international corn markets. In Brazil, due primarily to the increasing importance of the winter crop, the central-west region became the main corn producer in the country, overcoming the South, the main summer crop producer. On the international market, the increase in demand for the commodity - mainly in the Chinese and U.S. markets - also changed the behavior of prices worldwide. Based on all the aforementioned changes, we analyzed prices relationships in the corn spot and futures markets in the south and central-west regions of Brazil, between 2004 and 2016. We used various price discovery measures to find that Brazilian corn futures market leads the price information in the country. Our analysis for the spot market indicates that the South, represented by the production region of Cascavel, shows the highest share of price information, and therefore can be considered the primary reference in the price discovery process. However, we found that this result was not consistent, as the region of Rio Verde in the Center-West was the benchmark in the price discovery process during the period when summer crop production was higher than winter crop production (prior to 2011). We analyzed short-term price relationships using the Generalized Supremum Augmented Dickey-Fuller (GSADF) test to identify periods of speculative bubbles. Our results indicated the occurrence of several explosive episodes in all markets. In most cases such episodes were short-lived (lasting less than seven days), with differing characteristics, and had periods of both positive and negative bubbles. In addition, we identified periods when bubbles occurred simultaneously in all markets. This result indicates that there may also be a relationship between regional price volatilities. We expect that our results can be useful for those looking for references in price formation, and for improving commodity trading strategies in the cash market. In addition, once a bubble period is identified, traders can possibly use our results to build their expectations regarding the duration of bubbles and the average price variation (increase and decrease) within a bubble period.
Price discovery and speculation in the Brazilian corn market
Keywords: descoberta de preços; bolhas especulativas; mercado de milho; price discovery; speculative bubbles; corn market; Especulação agrária; Land speculation; Milho - Aspectos econômicos; Corn - Economic aspects; CIENCIAS SOCIAIS APLICADAS::ECONOMIA::ECONOMIAS AGRARIA E DOS RECURSOS NATURAIS; CIENCIAS SOCIAIS APLICADAS::ECONOMIA::METODOS QUANTITATIVOS EM ECONOMIA